Solid Substrate Production and Formulation of an Isolate of Metarhizium anisopliae for Biological Control of Stem Bug Tibraca limbativentris - Kruger, Raúl; Posadas, Julieta Beatriz; Angulo Lewylle, Maricel; Mini, Jorge Ignacio; Lecuona, Roberto Eduardo (IDOSI Publications, 2024)
One isolate of Metarhizium anisopliae (Ma 72) previously selected for its virulence against rice-stem bugs, Tibraca limbativentris, was studied. Its conidial production and quality parameters in several solid substrates, as well as its reusability, were evaluated. Conidial germination percentages (%G) in two experimental formulations - broken white rice and parboil rice - were evaluated at different storage times (0, 50 and 100 days) at 6°C and 20°C. Ma 72 was able to produce conidia in all the substrates. When used for the first time, the broken white rice presented the highest production parameters, with 4.4 x10 10 conidia/g conidial powder. Its production parameter was even higher than that of parboil rice (control). Nevertheless, when the substrates were reused, parboil rice presented the highest value. In both experimental formulations, the%G decreased from 97% to less than 87.32% and 85.11% at 6°C after 50 and 100 days of room storage, respectively. At 20°C the%G presented values below 51.42% and 16.47% after 50 and 100 days of storage, respectively. Only parboil rice could be reused successfully, but at a considerable cost. In contrast, broken white rice might be suitable as an economical substrate but would not be reused, thus probably increasing production wastes. Using broken white rice as part of a wettable powder formulation may reduce these wastes.